2013
DOI: 10.1109/tcc.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Stratus: Load Balancing the Cloud for Carbon Emissions Control

Abstract: Abstract-Large public cloud infrastructure can utilise power which is generated by a multiplicity of power plants. The cost of electricity will vary among the power plants and each will emit different amounts of carbon for a given amount of energy generated. This infrastructure services traffic that can come from anywhere on the planet. It is desirable, for latency purposes, to route the traffic to the data centre that is closest in terms of geographical distance, costs the least to power and emits the smalles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…Soni et al [10] addressed workload as a multiobjective problem comprising of number of tasks where each task must be finished within its deadline time. Authors have taken three objectives-to balance Load, maintaining request priority and minimizing the execution error.…”
Section: A Time and Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Soni et al [10] addressed workload as a multiobjective problem comprising of number of tasks where each task must be finished within its deadline time. Authors have taken three objectives-to balance Load, maintaining request priority and minimizing the execution error.…”
Section: A Time and Costmentioning
confidence: 99%
“…Their results achieved reduction of 26.41% energy consumption as compare standard PALB algorithm by reducing the number of power-on machines. J. Doyle et al [10] observed the challenge of receiving dynamic requests for cloud services across the globe, proposed the Stratus system based on Vornoi partitions. Their model details and minimizes the carbon emissions (carbon intensity-g/KWh), electricity cost, cooling cost and average job time taken for execution.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…Existing research addresses energy cost optimization [77,96,97,125], and joint optimization of energy cost and carbon footprint of data centers [39,46,69,78,100,127]. The existing cost-aware workload management solutions lack a mathematical analysis for the optimality of the solutions.…”
Section: Application Of the Solutionsmentioning
confidence: 99%
“…Carbon capping in data centers has recently received attention both in industry [3] and in literature [39,46,69,78,100,127]. Large data center operators took initiative to utilize renewable energy in data centers.…”
Section: Carbon Cappingmentioning
confidence: 99%
“…Often load-balancing policies consider web server systems as a target [11,26], where one of the most important result is to bound the maximum response time that the clients are exposed to [19]. Load-balancing strategies can be guided by many different purposes, for example geographical [2,33], driven by the electricity price to reduce the datacenter operation cost [15], or specifically designed for cloud applications [5,23,24].…”
Section: Related Workmentioning
confidence: 99%